Identifikasi Jenis Tumbuhan Obat Tradisional Yang Di Manfaatkan Untuk Mengobati Penyakit Pada Manusia Di Desa Naitimu Kecamatan Tasifeto Barat Kabupaten Belu - Novita Wattimena; Sardina Ndukang; Hildegardis Missa (Program Studi Pendidikan Biologi Universitas Katolik Widya Mandira, 2023)
Health is a basic need for human life. With the advancement of medical technology in humans, it is increasingly modern, so that more people choose to go to the hospital or to the health center because the treatment services are more efficient. With more efficient treatment, traditional medicine is rarely found. Even though this treatment is rarely found, some people still use this treatment, due to considerable economic limitations. Therefore it is necessary to add to the community's insight regarding how to manage traditional medicinal plants to treat diseases in humans. The purpose of this study was to determine the characteristics of the respondents, determine the potential of medicinal plant species, the parts used to treat diseases and find out the habitus found in the village. Your naitimu. The type of research used is descriptive research, namely by direct observation. The method used in this study is semi-structured interviews. The research procedures include determining key informants, determining respondents, research instruments, interviews, exploration, documentation, identification, description and classification. The results of the study found 15 respondents who had knowledge about medicinal plants with an uneven ratio of the number of male and female respondents, consisting of 7 male respondents and 8 female respondents. The use of medicinal plants by the community is widely known and practiced by people aged 45–49 years. Obtained 18 types of medicinal plants, namely: Cashew (western cashew), Moringa (Moringa oleifera), Lemongrass (Cymbopogon citratus), Soursop (Annona muricata), Aromatic ginger (Kaempferia galanga), Turmeric (Turmeric is long), Curcuma (Curcuma zanthorrhiza), Pawpaw (Upload papaya), Red Amber (Jatropha), Ginger (Zingiber officinale), Patikan Kebo (Euphorbia hirta), For-For (Cylindrical orders), Guava (Psidium guajava), Meniran (Phyllanthus niruri), Kirinyuh (Chromolaena odorata), Mimosa (Mimosa chaste), African Leaf (Vernonia amygdalina) and Basil (Ocimum basilicum). The part of the plant used is the leaves (Leaf), Rhizomes (Rhizomes), Wants (Radix), Young (Stem), and Fruit peel(Pericarpium). There are 4 plant habitus namely herbs, shrubs, shrubs and trees The conclusion from this study was that there were 15 respondents consisting of 7 men and 8 women. The use of medicinal plants by the community is widely known and carried out by people aged 45–49 years. There were 18 types of plants that have medicinal potential. The parts of the plant used are leaves, fruit skin, rhizomes, stems and roots. There are 4 plant habitus namely herbs, shrubs, shrubs and trees.